Suppression of stress granule formation is a vulnerability imposed by mutant p53 - Elizabeth Thoenen; Atul Ranjan; Alejandro Parrales; Shigeto Nishikawa; Dan A. Dixon; Sugako Oka; Tomoo Iwakuma (Nature Communications)
Abstract Missense mutations in the TP53 (p53) gene have been linked to malignant progression. However, our in-silico analyses reveal that hepatocellular carcinoma (HCC) patients with mutant p53 (mutp53) have better overall survival compared to those with p53-null (p53null) HCC, unlike other cancer types. Given the historical use of sorafenib (SOR) monotherapy for advanced HCC, we hypothesize that mutp53 increases sensitivity to SOR, a multikinase inhibitor that induces endoplasmic reticulum (ER) stress. Here we show that mutp53 inhibits stress granule (SG) formation by binding to an ER stress sensor, PKR-like ER kinase (PERK), and a key SG component, GAP SH3 domain-binding protein 1 (G3BP1), contributing to increased sensitivity of SG-competent cells and xenografts to ER stress inducers including SOR. Our study identifies a unique vulnerability imposed by mutp53, suggesting mutp53 as a biomarker for ER stress-inducing agents and highlighting the importance of SG inhibition for cancer treatment.